Ethnography of communication on an offshore oil platform: Bridging organizational communication to ESL pedagogical practices - Nordin, S.M. (Common Ground Publishing, 2013)
This study employs an ethnography of communication approach to capture the organizational culture and its cultural behaviour, as the approach acknowledges the link between language use and its cultural context. The purpose of the study is to obtain a description of the communicative processes and events in a homogenous speech community on an isolated offshore oil platform. An offshore oil platform is a restricted area that requires a safety license to be onboard, where the workforce has its own identity shaped by their working condition and organizational culture. The almost 300 employees stay together on the oil platform for a twoweek duration, away from their families, forming a distinct community with the purpose to attain the organizational production goal. The researcher stayed on the oil platform for three weeks to collect data based on participant observation and interviews. The unit analysis of this study is the communicative events, as communication in a community can be categorized into different kinds of events with different behavioral norms. The findings provide a rich insight into the communicative events on an offshore oil platform, within its unique organizational culture. The communication processes and events described will give a glimpse of the organizational subcultures, which include power distance, stress management, organizational commitment, and work culture. This crossdisciplinary paper about organizational communication and teaching English as second language will conclude with significant key take-aways for pedagogical implications. The discussion on the pedagogical implications, with the underlying theoretical framework of TBLT (task-based language teaching), contributes significantly to the body of literature and to language teachers, as it is based on an authentic research findings in a restricted working area beyond the classroom. Â© Common Ground, Shahrina Md Nordin, Roselind Wan.